(untitled) (SCIENTIA JOURNAL, 2020)
According to World Health Organization (WHO) explains that giving breastfeeding to babies aged 0 to 6 months without the other supplement. Based on the result of a research, known that international guidance recommend to giving exclusive breastfeeding during early six month based on scientific paper about benefit of breastfeeding for baby live immune, their growth and breast feeding gives all of energy and nutrition needed baby during early 6 month. Files of Jambi health breastfeeding profile that baby get exclusive breastfeeding as many as 36,94% on 2011, increase to 62,6% on 2012. Purpose of this research is to know the relationship[ between mother’s knowledge and job with giving breastfeeding to baby in Selincah Health Center Jambi on 2020. This method is analytic survey with cross sectional approach. Population in this research is all of mothers with their age 7-12 months babies, that come to selincah Health Center jambi on February 17-22 with 35 respondent as sample by accidental sampling. Analysis use univariate and bivariate analysis using Chi-Square statistic test with computerization with significant level α = 0,05 result of 35 respondents with giving exclusive breastfeeding 51,4% and un giving 48,6%. Mother with good knowledge as many as 57,1% and less knowledge 42,9%. Working mothers as many as 28,6% and un working mothers 71,4%. Result of bivariate analysis show that there’s significant relationship between knowledge with giving exclusive breastfeeding where p value 0,002 and no significant relationship between jobs with giving exclusive breastfeeding, where p value 1,000. From this research hoped that health worker do counseling on safe breastfeeding for working mothers so that working have the same opportunity to provide exclusive breastfeeding